The Energy and Mass Balance of Peruvian Glaciers. Issue 23 (2nd December 2021) - Fyffe, Catriona L.; Potter, Emily; Fugger, Stefan; Orr, Andrew; Fatichi, Simone; Loarte, Edwin; Medina, Katy; Hellström, Robert Å.; Bernat, Maud; Aubry‐Wake, Caroline; Gurgiser, Wolfgang; Perry, L. Baker; et al.
Abstract: Peruvian glaciers are important contributors to dry season runoff for agriculture and hydropower, but they are at risk of disappearing due to climate change. We applied a physically based, energy balance melt model at five on‐glacier sites within the Peruvian Cordilleras Blanca and Vilcanota. Net shortwave radiation dominates the energy balance, and despite this flux being higher in the dry season, melt rates are lower due to losses from net longwave radiation and the latent heat flux. The sensible heat flux is a relatively small contributor to melt energy. At three of the sites the wet season snowpack was discontinuous, forming and melting within a daily to weekly timescale, and resulting in highly variable melt rates closely related to precipitation dynamics. Cold air temperatures due to a strong La Niña year at Shallap Glacier (Cordillera Blanca) resulted in a continuous wet season snowpack, significantly reducing wet season ablation. Sublimation was most important at the highest site in the accumulation zone of the Quelccaya Ice Cap (Cordillera Vilcanota), accounting for 81% of ablation, compared to 2%–4% for the other sites. Air temperature and precipitation inputs were perturbed to investigate the climate sensitivity of the five glaciers. At the lower sites warmer air temperatures resulted in a switch from snowfall to rain, so that ablation was increased via the decrease in albedo and increase in net shortwave radiation. At the top of Quelccaya Ice Cap warming caused melting to replace sublimation so that ablation increased nonlinearly with air temperature. Key Points: Net shortwave radiation dominates the energy balance, although it is offset by dry season net longwave radiation and the latent heat flux Sites in the ablation area show a discontinuous wet season snowpack and wet season ablation is driven by precipitation dynamics The ablation response to warming is nonlinear due to reduced percentage snowfall and sublimation switching to melt at high elevations